Ideas Et Attitudes : Catalan Conceptual Art 1969 - 1981. - Parcerisas, Pilar; Snoddy, Stephen (Manchester : Cornerhouse, 1994)
Abad, Francesc ; Balcells, Eugènia ; Cerdà, Jordi ; Ferrer, Benet ; Benito, Jordi ; Eulàlia ; Domènech, Joseph ; García Sevilla, Ferran ; Miralda, Antoni ; Grup de Treball ; Noguera, Pere ; Miralles, Josefina ; Pablo, Jordi ; Muntadas, Antoni ; Pujol, Carles ; Pazos, Carles ; Rossell, Benet ; Ponsati, Josep ; Xifra, Jaume ; Rabascall, Joan ; Ribé, Angels ; Santos, Carles ; Torres, Francesc
biografie
Ideas Et Attitudes : Catalan Conceptual Art 1969 - 1981, Cornerhouse, Manchester, 30 April - 5 June 1994 ; John Hansard Gallery, University of Southampton, 2 August - 10 September 1994
Engels
boek
Keywords: Catalonië; Spanje